2013
DOI: 10.1038/bjc.2013.417
|View full text |Cite
|
Sign up to set email alerts
|

Reporting practices of pharmacodynamic studies involving invasive research procedures in cancer trials

Abstract: Background:Tumour biopsy for pharmacodynamic (PD) study is increasingly common in early-phase cancer trials. As they are non-diagnostic, the ethical justification for such procedures rests on their knowledge value. On the premise that knowledge value is related to reporting practices and outcome diversity, we assessed in a sample of recent invasive PD studies within cancer trials.Methods:We assessed reporting practices and outcomes for PD studies in a convenience sample of cancer trials published from 2000 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Despite an extensive search for all eligible studies, published or unpublished, it is possible that some studies were missed. Although less is known about the impact of publication bias in systematic reviews of pharmacodynamics studies, than in reviews of clinical trials, selective reporting has been documented and is a potential threat to validity [45,46]. Furthermore, many pharmacodynamics studies fail to report aspects of study methodology (e.g., blinding) that may have a bearing on the results.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an extensive search for all eligible studies, published or unpublished, it is possible that some studies were missed. Although less is known about the impact of publication bias in systematic reviews of pharmacodynamics studies, than in reviews of clinical trials, selective reporting has been documented and is a potential threat to validity [45,46]. Furthermore, many pharmacodynamics studies fail to report aspects of study methodology (e.g., blinding) that may have a bearing on the results.…”
Section: Discussionmentioning
confidence: 99%
“…Scheduling research biopsies in busy interventional radiology departments can be challenging—we demonstrate here that it is logistically possibly to do so, and centres received a standard per-biopsy fee of £800 (approximately US$1000, €950) to cover the cost of the scan (CT or ultrasound), the radiologist’s time, the biopsy needle and fixative. There is variation in the reporting of research biopsies ( Freeman et al , 2013 ), and we believe that it is essential that biomarker biopsy studies are reported consistently to improve future trials. Such reports should include complete details for biopsy sites, the number of biopsies, the protocol for tissue analysis and overall outcome.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have already demonstrated that image-guided biopsies can be obtained in patients with ovarian cancer ( Spencer et al , 2006 ; Griffin et al , 2009 ; Swisher et al , 2017 ), whilst many early phase clinical trials now include translational research biopsies to investigate pharmacodynamic biomarkers. However, there is widespread variation in the reporting of outcomes of biopsy-driven studies ( Freeman et al , 2013 ) and few data on the utility of these biopsies for complex genomic studies.…”
mentioning
confidence: 99%
“…Another study found that a minority of such studies used blinded histopathological assessment (16). This leaves analyses highly susceptible to risk of bias.…”
mentioning
confidence: 99%
“…Only a third of studies report results in full (17), and in a survey 40% of authors of publications involving invasive research procedures in cancer described incomplete reporting as occurring "more often than not." This is reinforced by the observation that most studies report pharmacodynamic experiments as positive (16). A deficit of negative results suggests either that researchers are not publishing negative findings or that researchers are using correlative studies to address questions for which answers are mostly already known at the outset of investigation.…”
mentioning
confidence: 99%